GlaxoSmithKline''s experience of incurred sample reanalysis for dried blood spot samples. (May 2011) - Barfield, Matthew; Ahmad, Sheelan; Busz, Maria
Dried blood spots are becoming a popular alternative to plasma for many different applications. This has been driven by animal ethics but also by ease of use and cost savings. Recent regulatory guidance now has a requirement for incurred sample reanalysis. This article details three examples of incurred sample reanalysis using dried blood spot samples.